2010
DOI: 10.1186/1743-422x-7-22
|View full text |Cite
|
Sign up to set email alerts
|

Detection of dengue virus in saliva and urine by real time RT-PCR

Abstract: Early diagnosis of dengue virus (DENV) infection is important for patient management and control of dengue outbreaks. The objective of this study was to analyze the usefulness of urine and saliva samples for early diagnosis of DENV infection by real time RT-PCR. Two febrile patients, who have been attended at the General Hospital of the School of Medicine of Ribeirao Preto, Sao Paulo University were included in the study. Serum, urine and saliva samples collected from both patients were subjected to real time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 10 publications
2
66
0
4
Order By: Relevance
“…The sequence results revealed that the nucleotide sequences of RT-PCR products were identical between urine and serum samples from respective patients, indicating that these represented the same infecting strain of DENV. We previously reported a dengue case with the detection of DENV-1 genome in urine samples on disease days 7, 8, and 14, a time when the genome was not detected in serum samples (11), and another group has also reported the detection of DENV genome in urine samples (12). In those studies, the number of studied cases was limited to one and two cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence results revealed that the nucleotide sequences of RT-PCR products were identical between urine and serum samples from respective patients, indicating that these represented the same infecting strain of DENV. We previously reported a dengue case with the detection of DENV-1 genome in urine samples on disease days 7, 8, and 14, a time when the genome was not detected in serum samples (11), and another group has also reported the detection of DENV genome in urine samples (12). In those studies, the number of studied cases was limited to one and two cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The use of urine samples for laboratory diagnostic testing has some advantages over the use of serum samples, such as ease of use and noninvasiveness. Our group and others have previously reported the detection of DENV genome in urine samples for a limited number of patients (11,12). In the present study, we attempted to determine the usefulness of urine samples in the laboratory diagnosis of DENV infection.…”
mentioning
confidence: 99%
“…Diagnosis of other viral infections in urine and saliva samples has been reported for human immunodeficiency virus (HIV), Hepatitis A, B, and C, and rubella [14][15][16][17][18][19][20], and more recently in other flaviviruses, West-Nile virus (WNV) [21][22][23] and Dengue (DENV) serotypes -1, -2, -3, and -4 [24][25][26][27][28][29][30][31][32][33][34][35]. WNV can be detected longer in urine than serum [21] and can be isolated from urine [22,23].…”
Section: Advantages Of Non-invasive Sample Collectionsmentioning
confidence: 99%
“…It was demonstrated by PCR that ZIKV -like in DENV infections -was detectable in urine and saliva of patients at about the 5th day after onset of symptoms [77][78][79][80][81]. Saliva samples can be of particular interest when serum is difficult to collect, especially from children and newborns.…”
Section: Other Transmission Routesmentioning
confidence: 99%